Weight discrimination, anticipated weight stigma, and disordered eating. (April 2020) - Hunger, Jeffrey M.; Dodd, Dorian R.; Smith, April R.
Abstract: Weight discrimination is a well-established risk factor for disordered eating cognitions and behaviors. However, little is known about what may account for this association. Recent research suggests that anticipated weight stigma may explain the relationship between weight discrimination and non-eating disorder related health outcomes; the present study seeks to replicate this premise and extend it to the disordered eating realm. In a non-clinical sample of adults in the United States ( N  = 297) we test the hypothesis that weight discrimination has an indirect association with eating disorder symptomatology through anticipated stigma. At a single timepoint, participants recruited from the online data collection platform SocialSci completed self-report, online surveys of weight discrimination in day-to-day life, anticipated weight stigma, eating disorder symptoms, and demographic information. As hypothesized, weight discrimination was indirectly associated with greater disordered eating symptoms via its association with anticipated weight stigma. This pattern of results held when controlling for gender, body mass index, and self-perceived weight status. These findings suggest that anticipated stigma is relevant in the association between weight discrimination and greater disordered eating. This premise deserves additional attention using methodological approaches that can facilitate stronger causal claims. We discuss the potential for this line of research to inform clinical interventions. Highlights: Weight discrimination is a well-established risk factor for disordered eating. Anticipating weight stigma may help explain why this relationship exists. We find anticipated weight stigma accounts for this association cross-sectionally. More robust research designs are needed to establish directionality and causality. If replicated, these findings may inform interventions for disordered eating.